Body Part Removal: A Thematic Exploration of U.K. Homicide Offenses - Almond, Louise (Journal of interpersonal violence, 2021)
Body part removal (BPR) is a rare homicide phenomena, which emerges as a result of a variety of motives. Fifty-eight BPR U.K. homicide cases were analyzed. Findings indicated key characteristics within BPR murder offenses, with most offenders males; aged around 31 years; knew their victims; with presence of alcohol, drugs, and mental health issues; and more than two thirds of the sample had previous convictions, more than 50% for theft. Offense behaviors showed “multiple wounds” and “victim naked” as highest frequency, with the head as the most frequently removed body part. Smallest space analysis (SSA) identified two behavioral themes (expressive and instrumental) with 62.1% of cases classified as one of these. The study has provided the largest U.K. sample of BPR homicide, furthering understanding this type of offense and the offenders who commit it.